Relationship between Academic Self-Concept and Academic Performance in Mathematics of Secondary School Students in Delta State, Nigeria - Ebele Chinelo Okigbo; Odiri E. Onoshakpokaiye (Universitas Tidar, 2023)
The study investigated the relationship between self-concept and the academic performance in mathematics of secondary school students in Delta State, Nigeria. Two research questions and two null hypotheses guided the study. A correlation design was adopted in the study. All 42,299 senior secondary two (SS2) mathematics students in the 2021/2022 session in the state made up the research population. A multistage sampling procedure was used to draw 1,650 of these students. The instrument utilized to gather data was the Academic Self-Concept Questionnaire (ASQ), which was validated by three experts. The instrument's dependability was determined using Cronbach’s Alpha, and the result was 0.68. The students’ performances in Mathematics for three terms in SS1 represent their performance scores in mathematics. The collected data were analyzed using Pearson product moment correlation and a t-test for correlation analysis. The results of the study showed a very low positive and no significant relationship between academic self-concept and the performance of secondary school students in mathematics. However, there was a significant difference in relation to mathematics performance between students with a positive self-concept and those with a negative self-concept in mathematics. In light of the results, it was recommended among other things, that mathematics teachers should make a deliberate effort to help students who possess negative self-concepts by conditioning, modeling, and changing their behaviors to perform better in mathematics.